Eficácia harmônica dos direitos fundamentais: direito civil e a interpretação constitucional na perspectiva do direito à propriedade e do bem de família do fiador - Mesquita, Renata Paccola (2012)
This paper has the objective of demonstratin, through doctrinal and jurisprudential analysis, the effect of fundamental rights in private relations, demonstrating, thereby, the necessity to harmonize principles considered eminently civilians with the constitutional norm. In this way, we start from the analysis of fundamental rights by inserting them in particular relations with strong reflection on the principle of private autonomy, who is relativize. In this context, it seeks to analyze the jurisprudence of the national courts, in order to contextualize the discussion, bringing out the occurrence of divergence between the judiciary and the understanding of national doctrine. It is through critical analysis of specific cases that it also shows the existence of conflict between rules, with the collision of fundamental principles that must be solved in the pursuit of higher conservation interests, and by considering the principle of proportionality. Finally, through the premises and the conflict between fundamental rights and autonomy, it is analyzed the possibility, or not, to take the family property from the guarantee of rent contract, due to the art. 3, VII of Law 8.009/90, It would lose the protection of immunity, because, freely, offer his property to assure the rent obligation